1981
DOI: 10.7164/antibiotics.34.1026
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of DL 473, a new semisynthetic rifamycin derivative.

Abstract: DL 473, a new semisynthetic rifamycin, was 2' 10 times more active in vitro than rifampicin (RAMP) against several clinical isolates of Mycobacterimn tuberculosis and only slightly less active than RAMP against Gram-positive and Gram-negative bacteria. It showed excellent therapeutic activity in mice in experimental infections caused by Staphylococcus aureus, Streptococcus pyogenes group A, Streptococcus pneumoniae and Klebsiella pneumoniae. In the experimental TB infection in the mouse DL 473 was clearly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Subsequent studies have shown that the broth-determined MICs of RPT were two-to threefold lower than those of RMP (8,10). The elimination half-life of RPT in animals and humans was about five times longer than that of RMP, and the levels of RPT in plasma substantially exceeded the MICs for a period of up to 72 h after a single oral dose (1)(2)(3)12). The advantage of RPT over RMP has been shown in murine models (1,5,11,18).…”
mentioning
confidence: 99%
“…Subsequent studies have shown that the broth-determined MICs of RPT were two-to threefold lower than those of RMP (8,10). The elimination half-life of RPT in animals and humans was about five times longer than that of RMP, and the levels of RPT in plasma substantially exceeded the MICs for a period of up to 72 h after a single oral dose (1)(2)(3)12). The advantage of RPT over RMP has been shown in murine models (1,5,11,18).…”
mentioning
confidence: 99%
“…have been investigated for their activities against Mycobacterium tuberculosis and Mycobacterium avium complex (MAC) in in vitro, macrophage, and animal models (1,3,8,10). In a similar attempt, the Chemical Pharmaceutical Research Institute, Sofia, Bulgaria, has developed a new rifamycin derivative, 3-(4-cinnamylpiperazinyl iminomethyl) rifamycin SV, which was called T9 (Fig.…”
mentioning
confidence: 99%
“…However, KRM-1648 was not efficacious in suppressing the progression of pulmonary lesions and the increase in bacterial loads at the sites of infection, including lungs and spleen, at the late phase of infection. This may imply some difficulty with chemotherapy for AIDSassociated MAC infection, even with KRM-1648 treatment, which has excellent in vitro and in vivo anti-MAC activities, as shown in the present study.Rifampin (RMP) and other rifarmycins, including rifabutin (RBT), rifapentine, and so on, are highly active against slowly growing mycobacteria, particularly Mycobacterium tuberculosis and some nontuberculous mycobacteria (1,3,5,7,14,18,24,28,29,36). However, they are not so excellent in their in vitro activity against M. avium complex (MAC) (5,19,28), supposedly because of the permeability barrier of the organisms (11,25).…”
mentioning
confidence: 99%
“…(RBT), rifapentine, and so on, are highly active against slowly growing mycobacteria, particularly Mycobacterium tuberculosis and some nontuberculous mycobacteria (1,3,5,7,14,18,24,28,29,36). However, they are not so excellent in their in vitro activity against M. avium complex (MAC) (5,19,28), supposedly because of the permeability barrier of the organisms (11,25).…”
mentioning
confidence: 99%